SPK REKRUTMEN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING BERBASIS WEBSITE - Lucas Lucas; Jeanny Pragantha; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
Employees are one of the most important elements in a company. So companies must be more selective in hiring the employees, because progress in a company can also be determined by the attitude of the employees. When recruiting employees, it is likely for the company to make the wrong decision especially when there are a lot of applicants.Therefore, a decision support system was created to provide better recommendations in recruitment process. The system uses Simple Additive Weighting (SAW) method which is one of the Fuzzy Multiple Attribute Decision Making Methods. The data used in this system is a combination between real data from PT. Jasa Cepat Internasional and dummy data.The application of the Simple Additive Weighting method is able to provide the recommendation results from predetermined criteria. The level of accuracy using Simple Additive Weighting method is also very accurate at 100%.